Prospects of organic acids as safe alternative to antibiotics in broiler chickens diet - Khan, Rifat Ullah; Naz, Shabana; Raziq, Fazal; Qudratullah, Qudratullah; Khan, Nazir Ahmad; Laudadio, Vito; Tufarelli, Vincenzo; Ragni, Marco (Environmental science and pollution research international, 2022)
Genetically, modern broilers are fast-growing birds which attain the market age at the age of 5 weeks. To maintain optimum production, antibiotics have been commonly included in the diets as growth promoters. However, due to the increase in antimicrobial resistance, their uses have been banned worldwide. To keep the optimum level of production and health in broiler industry, the use of alternative growth promoters such as probiotics, prebiotics, enzymes, and organic acids has been proposed. Chemically, organic acids are weak acids and only partially dissociate. They are considered safe and have been used for preservation of food for centuries. Nowadays, organic acids have been reported for antibacterial, immune potentiating, and growth promoters in broilers. In this review, the effects of dietary inclusion of organic acids on growth, nutrient digestibility, intestinal integrity, immune system, and antibacterial activity in broilers are discussed.